2016
DOI: 10.1038/srep33967
|View full text |Cite
|
Sign up to set email alerts
|

Origin of multi-level switching and telegraphic noise in organic nanocomposite memory devices

Abstract: The origin of negative differential resistance (NDR) and its derivative intermediate resistive states (IRSs) of nanocomposite memory systems have not been clearly analyzed for the past decade. To address this issue, we investigate the current fluctuations of organic nanocomposite memory devices with NDR and the IRSs under various temperature conditions. The 1/f noise scaling behaviors at various temperature conditions in the IRSs and telegraphic noise in NDR indicate the localized current pathways in the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…It is also obvious that the turn‐on process occurs through discrete events in which the current abruptly changes. The percolation conducting path models may explain the experimental results above. Every step increase in the current may represent a new current path formation.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…It is also obvious that the turn‐on process occurs through discrete events in which the current abruptly changes. The percolation conducting path models may explain the experimental results above. Every step increase in the current may represent a new current path formation.…”
Section: Resultsmentioning
confidence: 80%
“…Various experimental tools have been employed to investigate the fundamental properties of ORRAM devices; for example, impedance spectroscopy to directly probe the charge trapping in the active layer and a direct spatial mapping of the current paths within the layer via elemental analysis . We have recently employed 1/ f noise measurements to show that the conduction paths in organic nanocomposite memory devices form a percolation network from the resistance scaling of the 1/ f noise . A further study of time–dependent current fluctuation behaviors during the turn‐off process in the NDR region demonstrated that the percolating conduction paths dynamically changed before completely getting disconnected (i.e., OFF state) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that that the Green's functions, self-energies, and their derivatives will become scalars for transport in the single molecular energy level case and therefore the commutator term will vanish. We now consider the equation of motion for the lesser Green's function which is given by (17). The expansions (18) and (19) are substituted into (17) and, as before, split based on order to give…”
Section: B Non-adiabatic Expansion Of Kadanoff-baym Equations In Wigmentioning
confidence: 99%
“…We now consider the equation of motion for the lesser Green's function which is given by (17). The expansions (18) and (19) are substituted into (17) and, as before, split based on order to give…”
Section: B Non-adiabatic Expansion Of Kadanoff-baym Equations In Wigmentioning
confidence: 99%